G5 Use of anterior abdominal wall blocks in paediatric percutaneous endoscopic gastrostomy insertion. (12th September 2022) - Tse, Chi; Rivlin, Gillian; Copley, Sian; Byrne, Lauren; Skoutelis, Nikolaos; Rizvi, Iman; Ramsdale, Anya; Auth, Marcus; Cameron, Fiona; Cheng, Jeng; Renji, Elizabeth; Tamhne, Sarang; et al.
Abstract : Introduction: Anterior abdominal wall blocks (AAWB), including rectus sheath (RSB) and transverse abdominis plane (TAP) blocks are frequently used in surgical procedures including umbilical hernia repair and midline incision operations. AAWB is a well-recognised method of post-operative pain management. The European Society of Anaesthesiology 2018, recommends the use of local infiltration with a long-acting anaesthetic agent and an anterior abdominal wall block (RSB/TAP) in laparotomy where resources permit. Limited information is available for the use of AAWB blocks in pain management for paediatric percutaneous endoscopic gastrostomy insertion (PEG). Aim: This project intended to compare the outcomes following use of AAWB and local anaesthetic in paediatric PEG insertions compared to local anaesthetic (LA) alone. Primary outcomes measures were post-operative pain scores, breakthrough pain management during the first 12 hours post-procedure and length of hospital admission. Method: Patients undergoing Gastroenterology-inserted PEG were identified through operator diaries between November 2020 to November 2021. Records were reviewed to evaluate intra-operative analgesic agents, post-operative pain scores at 1, 4, 8 and 12 hours post-procedure and length of hospital stay. Results: 30 patients were identified. 18 received LA alone (bupivacaine, levobupivacaine or chirocaine) and 12 received combined pain management with LA and AAWB. Age range of patients was similar in the LA and combined groups (3 – 128 months and 4 - 170 months). Indication for gastrostomy were similar in both groups; faltering growth (11, 5), NG dependence (9, 6), unsafe swallow/feeding difficulties (5, 3). The average length of stay was longer in those with LA alone [2.2 (1 to 5 days)] compared to the combined group [1.9 (1 to 6 days)]. Discharge on day 1 was lower in LA compared to the combined group (38.9%, 58.3%), similar on day 2 (27.7%, 25%) and a higher proportion stayed for greater than 3 days (33.3%, 16.7%). Breakthrough pain relief during the first twelve hours post-procedure included intravenous morphine (5.6% [LA] versus 0%[combined]), oral morphine (27.8% [LA] versus 16.7% [combined]), intravenous paracetamol (33.3% [LA] vs 58.3%[combined]), oral paracetamol (72.2% [LA] vs 75% [combined]), ibuprofen (33.3% [LA] vs 50%[combined]) and rectal diclofenac (5.6% [LA] vs 8.3%[combined]). Positive pain scores at 1, 4, 8 and 12 hours were similar; LA [16.7%, 16.7%, 11.1%, 0%] and combined [16.7%, 25%, 8.3%, 8.3%]. Conclusion: On average patients who had AAWB had a reduced length of stay and were more likely to be discharged on day 1. This is also shown in patients who stayed for two or more days. The results have shown a lower requirement of intravenous opiates in patients with AAWB compared to those who had a local anaesthetic. Use of non-opiate pain relief was similar in both groups. This might reflect standard pain management protocol. Assessment of pain scoring was similar across both groups. However, pain scoring is subjective and can be difficult to standardise amongst clinicians. Our sample size is currently restricted to 30 patients. We plan to expand our data collection to prospectively evaluate outcomes associated with AAWB versus LA alone, prior to its uniform implementation in practice.